(untitled) (City Dental College Journal, 2013)
Class III malocclusions are considered one of the most complex and difficult orthodontic problems to diagnose and treat. Skeletal and /or dental asymmetries in patient presenting with Class III malocclusion can worsen the prognosis recognizing the dentoalveolar and skeletal characteristics of class III malocclusion and their treatment possibilities is essential for a favorable nonsurgical correction. Therefore, this case presents a nonsurgical extraction approach to class III malocclusion treatment which can significantly improve the occlusion and facial deformities. A male patient of 18 yrs attended a private dental office at Dhaka, Bangladesh with the complain of aesthetic problem. On examination, incisor, canine and molar relationships were found Class III on both sides with palatally placed upper central incisors and crowding on both anterior segments. The case was treated orthodontically. It tooks nearly 18 months to complete the treatment. The patient was happy with the new appearance and function. DOI: http://dx.doi.org/10.3329/cdcj.v10i2.16349 City Dent. Coll. J Voume-10, Number-2, July-2013